1991
DOI: 10.1097/00000658-199103000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C as an Adjuvant Treatment to Resected Gastric Cancer

Abstract: Seventy consecutive patients were entered in a two-arm randomized trial after surgical resection for locally advanced gastric cancer. In the first arm, 37 patients were included as a control group, receiving no further treatment after surgery. In the second arm, 33 patients were treated with adjuvant chemotherapy consisting of mitomycin C (MMC), 20 mg/m2 administered intravenously once every 6 weeks for four consecutive cycles. All patients in both arms were followed in the same way for 5 years. At 5 years 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 9 publications
3
18
1
1
Order By: Relevance
“…The treated patient group, moreover, had relatively fewer hepatic metastases than the controls, which, in agreement with Coombes et al (1990) and Estape et al (1991), suggests a protective effect of adjuvant chemotherapy on blood-borne cancer dissemination. Acute toxicity was mild and treatment was well tolerated by patients, all of whom were treated on an outpatient basis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The treated patient group, moreover, had relatively fewer hepatic metastases than the controls, which, in agreement with Coombes et al (1990) and Estape et al (1991), suggests a protective effect of adjuvant chemotherapy on blood-borne cancer dissemination. Acute toxicity was mild and treatment was well tolerated by patients, all of whom were treated on an outpatient basis.…”
Section: Discussionsupporting
confidence: 88%
“…The attempt to reduce recurrences and prolong survival in patients with gastric carcinoma has led to intensive study of adjuvant chemotherapy after surgical gastric resection by cooperative groups and others (The Gastrointestinal Tumor Study Group 1982;Engstrom et al, 1985;Coombes et al, 1990;Estape et al, 1991). Although the overall results of these trials failed to demonstrate a general advantage and no clearcut benefits have emerged from trials involving random assignment to various adjuvant chemotherapy schedules (Alexander et al, 1993), such an approach seemed to be effective for certain subgroups of patients (de Braud et al, 1992).…”
mentioning
confidence: 99%
“…If the drugs have a more pronounced antitumour effect and if the amount of residual tumour after surgery is smaller, there ought to be a more apparent effect in earlier stages. This was seen in one Japanese study in 1984 (38), but in an earlier study the same authors found a better effect in more advanced stages, which is in accordance with several more recently published studies (26,31,43,51). Thus, there is no clear indication that a more pronounced drug effect is correlated to more extensive surgery or earlier disease.…”
Section: Comments On the Included Studiessupporting
confidence: 88%
“…No attempt was made to identify ongoing trials with unpublished results. For studies published more than once during follow-up, only the last: nal version, or the one presenting the most detailed results, have been included (24)(25)(26)(27)(28)(29)(30)(31). Two studies included in the earlier meta-analysis (23), one using immuno-therapy and the other only published in Japanese, were excluded in this analysis.…”
Section: Comments On the Included Studiesmentioning
confidence: 99%
“…The 5-year survival was 30% for surgery alone compared to 80% for MMC treated patients. The effect of treatment is still evident after 10 years of follow-up (Estape et al, 1991). The treatment was well tolerated and toxicity was only acute and mild.…”
mentioning
confidence: 94%